2015
DOI: 10.1371/journal.pone.0145041
|View full text |Cite
|
Sign up to set email alerts
|

Proportional Topology Optimization: A New Non-Sensitivity Method for Solving Stress Constrained and Minimum Compliance Problems and Its Implementation in MATLAB

Abstract: A new topology optimization method called the Proportional Topology Optimization (PTO) is presented. As a non-sensitivity method, PTO is simple to understand, easy to implement, and is also efficient and accurate at the same time. It is implemented into two MATLAB programs to solve the stress constrained and minimum compliance problems. Descriptions of the algorithm and computer programs are provided in detail. The method is applied to solve three numerical examples for both types of problems. The method shows… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(119 citation statements)
references
References 46 publications
6
112
1
Order By: Relevance
“…Finite element (FE) analysis (ANSYS, Canonsburg, PA) is used to retrieve the mechanical properties of the implant at each iteration. The PTO [37] is here extended to solve a problem where constraints of pore size, porosity, and strut thickness are converted into lower and upper bounds of element density, with two density-update strategies constructed ad hoc to handle the interface failure and fatigue constraints. The interface failure constraint is also introduced to prevent bone-implant micromotion, and the fatigue constraint is applied to the microlattice structure to guarantee the strength necessary to sustain the physiological set of mechanical loadings.…”
Section: Optimization Scheme For Graded-density Hip Implant With Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…Finite element (FE) analysis (ANSYS, Canonsburg, PA) is used to retrieve the mechanical properties of the implant at each iteration. The PTO [37] is here extended to solve a problem where constraints of pore size, porosity, and strut thickness are converted into lower and upper bounds of element density, with two density-update strategies constructed ad hoc to handle the interface failure and fatigue constraints. The interface failure constraint is also introduced to prevent bone-implant micromotion, and the fatigue constraint is applied to the microlattice structure to guarantee the strength necessary to sustain the physiological set of mechanical loadings.…”
Section: Optimization Scheme For Graded-density Hip Implant With Cellmentioning
confidence: 99%
“…Design Variables. The PTO, a simple and efficient nonsensitivity method, has been recently used to solve the classical minimum compliance problem and the stress constrained problem for a solid material [37]. In this paper, the PTO is extended to solve maximum compliance problem of a lattice domain under multiple constraints including interface failure and fatigue, two constraints that were not previously examined [37].…”
Section: Proportional Topology Optimization With Continuousmentioning
confidence: 99%
See 1 more Smart Citation
“…Both SIMP and level set methods are a common approach to seek an optimal layout of the structure by requiring sensitivity analysis and level set function for updating the design variable in each iteration, respectively. Stress limitation for linear analysis (yield stress) was applied to be an optimization constraint subject to minimize structural weight by employing SIMP approach with sensitivity [6] and non-sensitivity analysis [7]. The problems under stress and volume constraints acquired the quite different optimal layout.…”
Section: Introductionmentioning
confidence: 99%
“…A non-sensitivity method based on topology optimization, so-called proportional topology optimization (PTO) was introduced to update the value of each design variable. This method was investigated under the problem of stress constraint and compliance minimization, and the optimal layout of each problem was compared to the topology optimization with optimality criteria method (OC) [20]. It is found that the PTO method is an efficient algorithm to acquire the final results under topology optimization and more facile to implement the algorithm than the OC method.…”
Section: Introductionmentioning
confidence: 99%